2013
DOI: 10.1097/mat.0b013e31828a6e74
|View full text |Cite
|
Sign up to set email alerts
|

Improved Hemodynamics With a Novel Miniaturized Intra-aortic Axial Flow Pump in a Porcine Model of Acute Left Ventricular Dysfunction

Abstract: Currently, long-term mechanical circulatory support (MCS) is limited to large, complex devices that require invasive, high-risk surgical implantation. These devices are mainly used in patients with late stage heart failure (HF). We are developing a novel percutaneous intra-aortic micro-axial fluid entrainment pump intended for long-term MCS in patients with earlier stage HF. This study examined the pump's hemodynamic effects in a porcine model of acute HF. In three porcine experiments, the pump was deployed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The device is powered and controlled via a 2 mm electrical lead attached to the device, a lead that is envisioned to be tunneled out of the body for short‐term implantation of the device for support therapy in the future. Prior animal studies with this device demonstrated improvement in ejection fraction, cardiac output, and reduced myocardial oxygen extraction, along with improved urine output and renal perfusion . As the device does not traverse the ascending aorta or the great vessels, there is minimal risk of ischemic cerebrovascular accident.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The device is powered and controlled via a 2 mm electrical lead attached to the device, a lead that is envisioned to be tunneled out of the body for short‐term implantation of the device for support therapy in the future. Prior animal studies with this device demonstrated improvement in ejection fraction, cardiac output, and reduced myocardial oxygen extraction, along with improved urine output and renal perfusion . As the device does not traverse the ascending aorta or the great vessels, there is minimal risk of ischemic cerebrovascular accident.…”
Section: Discussionmentioning
confidence: 98%
“…Following PCI, Aortix is removed in the catheter lab and a percutaneous closure is performed. Initial safety and efficacy data were obtained in a porcine model and demonstrated proof of concept ( n = 9) …”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…While the RCP is designed as a temporary cardiac and renal support device, there are other devices in early development aiming to improve renal blood flow and aid decongestion in the longer term. These include the Procyrion Aortix device (Texas, USA) (25) and the Second Heart Assist device (California, USA). While they share an implantation position within the descending aorta, there are differences in impeller design and therefore operational speeds, and the degree of cardiac and renal support.…”
Section: Limitationsmentioning
confidence: 99%
“…Similar to a balloon pump, the device is positioned in the suprarenal portion of the descending aorta. The Aortix can support up to 5.0 L/min of pump flow thus potentially providing tissue perfusion and unloading of the left ventricle not achievable in the same magnitude by IABP.Initial small studies in animal models of the Aortix device confirmed increased cardiac output and renal perfusion and decreased cardiac stroke work and afterload, suggesting that the pump could improve heart failure outcomes and may help disrupt the cardiorenal syndrome cycle 2. The authors were able to show that the device can be implanted quickly and can support high-risk PCI.…”
mentioning
confidence: 99%